Invariant subspaces of finite codimension in Banach spaces of analytic functions - Carlsson, Marcus (Journal of mathematical analysis and applications, 2011)
We give a characterization of invariant subspaces of finite codimension in Banach spaces of vector-valued analytic functions in several variables, where invariant refers to invariance under multiplication by any polynomial. We obtain very weak conditions under which our characterization applies, that unifies and improves a number of previous results. In the vector-valued case, the results are new even for one complex variable. As a concrete application in several variables, we consider the Bergman space on a strictly pseudo-convex domain, and we improve previous results (assuming C ∞ -boundary) to the case of C 2 -boundary.